2004
DOI: 10.1215/s0012-7094-04-12317-6
|View full text |Cite
|
Sign up to set email alerts
|

Family Gromov-Witten invariants for Kähler surfaces

Abstract: We prove a structure theorem for the Gromov-Witten invariants of compact Kähler surfaces with geometric genus p g > 0. Under the technical assumption that there is a canonical divisor that is a disjoint union of smooth components, the theorem shows that the GW invariants are universal functions determined by the genus of this canonical divisor components and the holomorphic Euler characteristic of the surface. We compute special cases of these universal functions.Much of the work on the Gromov-Witten invariant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(87 citation statements)
references
References 29 publications
2
85
0
Order By: Relevance
“…In [4], using twisted family of K3 surfaces Bryan-Leung introduced the family GW-invariants of a K3 surface. Later, by deforming almost complex structures of surfaces Lee introduced the family GWinvariants of surfaces with p g > 0 [12]. For the case of K3 surfaces, Lee showed that the two versions of family GW-invariants coincide.…”
Section: Comment On Reduced Gw-invariants Of K3 Surfacesmentioning
confidence: 99%
“…In [4], using twisted family of K3 surfaces Bryan-Leung introduced the family GW-invariants of a K3 surface. Later, by deforming almost complex structures of surfaces Lee introduced the family GWinvariants of surfaces with p g > 0 [12]. For the case of K3 surfaces, Lee showed that the two versions of family GW-invariants coincide.…”
Section: Comment On Reduced Gw-invariants Of K3 Surfacesmentioning
confidence: 99%
“…Proof. This proof is similar to that of Lemma 3.2 in [LP1]. Use the same notation α for the real part of the holomorphic 2-form α on N D .…”
Section: Moduli Spacesmentioning
confidence: 64%
“…The index relations between simple J -holomorphic curves and their multiple covers make the following conjecture plausible: 1 CONJECTURE 1.1. On any closed symplectic manifold .M; !/ of real dimension at least 4, there exists a Baire subset J reg in the space of smooth !-tame almost complex structures such that for all J 2 J reg , every closed, connected, and simple J -holomorphic curve with deformation index 0 is super-rigid.Some special cases of this conjecture have been proved previously by Lee and Parker [16,17] and Eftekhary [5]. The techniques used in the present paper are related to those of [16,17], which also play a role in the announced solution by Ionel and Parker to the Gopakumar-Vafa conjecture [13].For an unbranched cover of a simple curve, the super-rigidity condition is equivalent to the usual notion of Fredholm regularity, and our main result (stated as Theorem 1.3 below) is that this can always be achieved by choosing J generically.…”
mentioning
confidence: 59%